Need for Integration of Indigenous Healing Into Western Psychosocial Interventions in Trauma Healing Among Victims of Armed Conflict in South Sudan - Kamwaria, Alex N.; Mutua Francis B. (Journal of Educational Policy and Entrepreneurial Research (JEPER), 2015)
The epistemological terrain upon which indigenous and Western psychosocial approaches in trauma healing traverse is not level. This has resulted in superficial dichotomies between the two healing approaches, thereby obscuring opportunities for an integrated approach that provides holistic trauma healing. The victims of armed conflict in south Sudan do not have vocabulary for a pathogen such as post-traumatic stress disorder (PTSD). For them trauma is closely linked to experiences of life such as poverty, hunger, separation of families, and failure to perform necessary rituals. In order to effectively heal the traumas, there is need to integrate indigenous healing into Western psychosocial healing approaches. The study notes that in this era of increasing globalization, transnational migration, and cultural diversity, it is crucial that trauma healers move beyond the western oriented therapeutic protocols and models and forge links with local community-based healing systems
Keywords: Psychosocial healing; Indigenous healing; Post-traumatic stress disorder